PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP DISIPLIN KERJA (STUDI KASUS PNPM MANDIRI PERDESAAN PERTANIAN DI PROVINSI PAPUA DAN PROVINSI PAPUA BARAT) - Tulus P.J. Sihombing (Operations Excellence: Journal of Applied Industrial Engineering, 2014)
Abstract. Field Program has strategic role in improving the income poor farmersin the land of Papua. Work motivation, working environment and work disciplinewill help escort in program activities. Research to know the influence ofmotivation of work, and workplace against discipline of work. Study on NationalSociety Empowerment Program Rural Agriculture in Papua Province and WestPapua Province. Independent variables consists work motivation and Workenvironement, with work discipline as dependent variable. The sampling methodused is saturated and sample of respondents who provide the answer as many as58 people of respondents. The method of analysis used in this study is multiplelinear regression. The research results showed indicate the presence of thepositive significant effect or influence of working environment in partial againstdiscipline of work. The two of variables consits work motivation and workenvironment jointly showed significant effect to work discipline. Workenvironment give stir the very great work discipline. While work motivation bypartial not influence to work discipline work.Keywords: Motivate The Job, Environmental Work and Discipline Work